Classification of Functional Products for Children's Food - Nazirova Rahnamohon Mukhtarovna; Usmonov Nodirjon Botiralievich; Musayeva Iroda (Genius Journals, 2022)
This article provides a classification of children's functional food products, their importance for a growing child's body. An overview of the baby food market is also given. The requirements for raw materials intended for the production of baby food are given.
Keywords: Food; baby food; functionality; safety